2004
DOI: 10.1073/pnas.0404888101
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen prevents bone loss through transforming growth factor β signaling in T cells

Abstract: Estrogen (E) deficiency leads to an expansion of the pool of tumor necrosis factor (TNF)-producing T cells through an IFN-␥-dependent pathway that results in increased levels of the osteoclastogenic cytokine TNF in the bone marrow. Disregulated IFN-␥ production is instrumental for the bone loss induced by ovariectomy (ovx), but the responsible mechanism is unknown. We now show that mice with T cell-specific blockade of type ␤ transforming growth factor (TGF␤) signaling are completely insensitive to the bone-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 54 publications
11
146
2
6
Order By: Relevance
“…In support of a role of T cells in the bone loss induced by E deprivation are reports from our laboratory that ovx fails to induce trabecular and cortical bone loss in nude mice (17,24,25,44) and in WT mice treated with abatacept (43), an agent that blocks T-cell costimulation and induces T-cell anergy and apo- ptosis (46,47). An independent confirmation of the role of T cells was provided by Yamaza et al (26), who reported that ovx fails to induce bone loss in nude mice and WT mice in which T-cell activation was blocked by aspirin.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In support of a role of T cells in the bone loss induced by E deprivation are reports from our laboratory that ovx fails to induce trabecular and cortical bone loss in nude mice (17,24,25,44) and in WT mice treated with abatacept (43), an agent that blocks T-cell costimulation and induces T-cell anergy and apo- ptosis (46,47). An independent confirmation of the role of T cells was provided by Yamaza et al (26), who reported that ovx fails to induce bone loss in nude mice and WT mice in which T-cell activation was blocked by aspirin.…”
Section: Discussionmentioning
confidence: 91%
“…This phenomenon results from enhanced thymic-dependent differentiation of BM-derived progenitors and peripheral expansion of mature T cells (41,42). Ovx causes the peripheral expansion of T cells by enhancing antigen presentation through increased expression of MHCII (41,43), which, in turn, is driven by a complex mechanism that involves increased production of IFN-γ and IL-7, blunted generation of TGF-β in the BM (22,25,41,44), and up-regulation of the costimulatory molecule CD80 on dendritic cells secondary to increased oxidative stress (43,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a significant number of reports demonstrating the interactions/cross-talk between estrogens and TGFβ signaling pathways in bone [Oursler et al, 1991b;Hughes et al, 1996;Oursler, 1998;Gao et al, 2004;Janssens et al, 2005]. Cross-talk between E 2 and TGFβ occurs at several levels, as depicted in Figure 1A and as described in detail below.…”
Section: Cross-talk Between the E 2 And Tgfβ Signaling Pathwaysmentioning
confidence: 97%
“…This increase in TGFβ production then acts on the surrounding OB cells to activate the TGFβ signaling pathway. The E 2 activation of the TGFβ signaling pathway via induction of TGFβ gene expression has been shown in numerous tissues, including trophoblasts [Rama et al, 2004], bone marrow and prostatic stromal cells [Hong et al, 2004], mouse T cells [Gao et al, 2004], mouse mesenchymal cells [Eger et al, 2004], and mouse adipocytes [Okazaki et al, 2002].…”
Section: Level 1 Cross-talk: E 2 Induction Of Tgfβ In Ob and Other Cementioning
confidence: 99%